2014
DOI: 10.1103/physrevb.90.035204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the DFT +  U formalism for modeling hole polarons in perovskite oxides

Abstract: We investigate the formation of self-trapped holes (STH) in three prototypical perovskites (SrTiO3, BaTiO3, PbTiO3) using a combination of density functional theory (DFT) calculations with local potentials and hybrid functionals. First we construct a local correction potential for polaronic configurations in SrTiO3 that is applied via the DFT+U method and matches the forces from hybrid calculations. We then use the DFT+U potential to search the configuration space and locate the lowest energy STH configuration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 56 publications
10
96
0
Order By: Relevance
“…(i) In titanates ATiO 3 (A = Pb, Ba, Sr), Erhart et al [13] have shown that LDA+U , with U = 8 eV, can be used to simulate oxygen-type self-trapped small hole polarons, reproducing in a satisfactory manner the results obtained on these entities by the hybrid HSE06 functional.…”
Section: ••mentioning
confidence: 98%
See 3 more Smart Citations
“…(i) In titanates ATiO 3 (A = Pb, Ba, Sr), Erhart et al [13] have shown that LDA+U , with U = 8 eV, can be used to simulate oxygen-type self-trapped small hole polarons, reproducing in a satisfactory manner the results obtained on these entities by the hybrid HSE06 functional.…”
Section: ••mentioning
confidence: 98%
“…This is related to the band-gap problem, more precisely to the incorrect position of the valence band maximum, formed by oxygen-2p states, obtained with GGA. Moreover, density functional theory (DFT) at its local and semilocal level of approximation (LDA, GGA) is unable to capture the localized oxygen-type hole polarons, while hybrid functionals such as PBE0 or HSE06 are able to [13,14]. This is mainly due to the self-interaction error that local and semilocal functionals exhibit.…”
Section: ••mentioning
confidence: 99%
See 2 more Smart Citations
“…In this letter, we employ the DFT+U Hubbard correction formalism developed by P. Erhart et al 24 performed using the Vienna Ab initio Simulation package (VASP), together with the projector augmented wave method (VASP-PAW) [25][26][27][28] and GGA-PBE for exchange and correlation. 29 First, we present the results of calculations for the perovskite CH 3 NH 3 PbI 3 , which is a benchmark absorber for solar cell devices.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%